2010
DOI: 10.1007/s00011-010-0284-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine (CCR) and fractalkine (CX3CR) receptors and end stage renal disease

Abstract: These results highlight the role of CCR5 and CX3CR1 in ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Cytokine genotypes have been studied in patients undergoing solid organ transplantation and certain polymorphisms have been implicated in the development of graft failure/survival . Presently, there are no laboratory assays proficient in predicting the incidence of acute/chronic rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine genotypes have been studied in patients undergoing solid organ transplantation and certain polymorphisms have been implicated in the development of graft failure/survival . Presently, there are no laboratory assays proficient in predicting the incidence of acute/chronic rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that genetic factors are involved in the onset of ESRD (Borkar et al, 2011;George and Mittal, 2011;Prakash et al, 2012). As a disorder that impairs all metabolic processes associated with vitamin D, ESRD is unsurprisingly associated with vitamin D deficiency (Dusilová Sulková, 2012), which can lead to a series of complications in patients with renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…4 Patients with ESRD display enhanced genomic damage, and DNA repair gene polymorphisms may affect DNA repair capacity and modulate susceptibility to ESRD. 5 Some investigations [6][7][8] suggested that genetic factors might play a key role in the onset of ESRD.…”
Section: Introductionmentioning
confidence: 99%